Instructional Leadership Of The School Principal In Improving Teacher Performance Meta-Analysis - Nur Muhammad Najmi Muhajir; Anis Zohriah; Rijal Firdaos (Mudir : Jurnal Manajemen Pendidikan, 2024)
This research aims to analyze how strong the principal's instructional leadership correlation is with teacher performance. This research uses quantitative methods with a meta-analysis approach using JASP 0.18.1.0 software. By using a meta-analysis approach we will find out general conclusions with a wider scope regarding how strong the correlation of the variables we are testing is. The data found were 20 articles through searches on Google Scholar and Mendeley search as well as SinceDirect with the keywords Internal Leadership and teacher performance. 10 articles were selected based on predetermined researcher characteristics and criteria. The data taken from the selected articles is the number of samples (N) and the r value for each article, then the effect size is analyzed. Data objects include; educational institutions, both general and Islamic educational institutions. Data from research on principals' instructional leadership on teacher performance were analyzed in depth to find the correlation between principals' instructional leadership on teacher performance. This research begins by formulating a research topic, exploring relevant research results for analysis. Data were analyzed using quantitative descriptive analysis. The research results show that the principal's instructional leadership is able to improve teacher performance. Based on the results of the analysis of the principal's instructional leadership on teacher performance. The results of the analysis using the random effect model show that there is a significant positive correlation between the principal's instructional leadership correlation with the performance of teacher Z; 3.913, P; <0.001; 95% (0.197; 0.591).